(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
The present method comparison study was carried out in the Radiology and Imaging Department of Dhaka Medical College & Hospital, Dhaka during the period of January 2012 to December 2013 to evaluate the role of Magnetic Resonance Imaging in the diagnosis of cervical disc herniation. A total of 40 patients having clinical features of cervical disc herniation with neck pain referred to the Department of Radiology & Imaging for MRI of their cervical spine were included in the study. At first all the patients were evaluated by detail history and clinical examination with special emphasis on clinical features. Then subsequently MRI of cervical spine was performed in all cases. The MRI report was checked by a competent radiologist of the department of Radiology and imaging DMCH. Among these 40 patients 11 were operated in department of neurosurgery, DMCH and 29 were operated in spine surgery unit, Department of Orthopaedic, BSMMU, Dhaka. The MRI and peroperative findings of these 40 patients were analyzed for the study. MRI findings correlated well in most of the cases with preoperative findings. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy of MRI in the diagnosis of cervical disc herniation were 94.12%, 83.33%, 96.97%, 71.43% and 92.5% respectively. Therefore it can be concluded that MRI may be used as a reliable tool with which we can assess the level, type and position of cervical disc herniation and can plan the subsequent appropriate management in majority of cases. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i2.21071